(untitled) (Journal of Philosophy Culture and Political Science, 2024)
The general picture of youth problems in the program documents of participants in the elections of deputies and parties held in the Majilis of the Republic of Kazakhstan is analyzed. The study found that political parties improperly ignored the interests of young people. The refusal of political parties to take into account the problems of youth leads to political apathy and an increase in discontent. Parties have the opportunity to enlist the support of young people in elections by developing specific strategies aimed at solving youth problems such as education, employment, housing and social services, based on theories of social policy development. Within the framework of this study, such research methods are used as a comparative analysis of the programs of the parties that participated in the elections in 2021 and 2023, a meaningful analysis of texts in party documents, a content analysis of words and concepts used in the Youth program and their problems, a quantitative analysis of the word “youth” in the text, a mutual comparative analysis of programs parties. According to the results of the research work, it became known that among the parties that passed the Majors of the Republic of Kazakhstan in 2021 and 2023, except for the Amanat party (formerly Nur Otan), they did not pay attention to solving youth problems in their election programs. The Amanat party noted the main problems of youth, took into account that they need to be solved, but did not voice all the issues. It was also discovered that this was the only party that often used the word ”youth". In general, the Amanat party, which has covered the problems of youth a lot, proposed concrete steps to solve the 2 main problems of youth. The other parties propose only declarative measures. Keywords: youth problems, parties, political reforms, election program, electoral system